1976
DOI: 10.1128/aac.10.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Activity In Vitro of Ticarcillin, BL-P1654, and Carbenicillin

Abstract: The activity of ticarcillin, BL-P1654, and carbenicillin was compared in vitro using a microtiter tube dilution test in Mueller-Hinton broth against 50 recent clinical isolates each of Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, Klebsiella species, Enterobacter species, Proteus species, and Pseudomonas aeruginosa. Bactericidal end points were determined using a modified Steers replicator. Ticarcillin was generally two to four times more active against all organisms tested except S. epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1978
1978
1989
1989

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…We have examined the efficacy and tox icity of high-dose amikacin regimens plus ticarcillin in experimental tricuspid valve PA IE, in hopes of taking advantage of the superior in vitro activity of ticarcillin (ver sus carbenicillin) aginst PA [9], and the possibly higher therapeutic: toxic ratio of amikacin (versus gentamicin or tobramy cin) [15]. The present study demonstrated several interesting findings: (1) amikacinticarcillin regimens are effective in experi mental right-sided PA endocarditis; (2) high-dose amikacin regimens demonstrat ed no enhanced efficacy over standarddose regimens; (3) no increase in nephro toxicity was seen with use of the high-dose amikacin regimens, and (4) there was no demonstrable difference in posttherapy vegetation cultures with high-dose com pared to standard-dose amikacin regi mens.…”
Section: Discussionmentioning
confidence: 99%
“…We have examined the efficacy and tox icity of high-dose amikacin regimens plus ticarcillin in experimental tricuspid valve PA IE, in hopes of taking advantage of the superior in vitro activity of ticarcillin (ver sus carbenicillin) aginst PA [9], and the possibly higher therapeutic: toxic ratio of amikacin (versus gentamicin or tobramy cin) [15]. The present study demonstrated several interesting findings: (1) amikacinticarcillin regimens are effective in experi mental right-sided PA endocarditis; (2) high-dose amikacin regimens demonstrat ed no enhanced efficacy over standarddose regimens; (3) no increase in nephro toxicity was seen with use of the high-dose amikacin regimens, and (4) there was no demonstrable difference in posttherapy vegetation cultures with high-dose com pared to standard-dose amikacin regi mens.…”
Section: Discussionmentioning
confidence: 99%
“…Ticarcillin is a more potent antipseudomonal agent than carbencillin when tested in vitro [13], and has clinical efficacy comparable to that of piperacillin in conjunction with an aminoglycoside in febrile neutropenic cancer patients [5]. Cefamandole Recognising the potentially broad-spectrum efficacy of the combination of ticarcillin and cefamandole, this prospectively randomised study was undertaken to define -~~ Most previous reports contained a majority of leukemic patients, whereas solid-tumour patients represent an Older and more heterogenous group, generally with From the Department of Clinical Oncology, Royal North Shore Hosbrief periods of moderate neutropenia following myelo-pital of Sydney, st. Leomrds whether the addition of tobramycin influenced efficacy and toxicity in a population of febrile neutropenic patients with solid tumours.…”
Section: Introductionmentioning
confidence: 99%
“…Ticarcillin is a more potent antipseudomonal agent than carbencillin when tested in vitro [13], and has clinical efficacy comparable to that of piperacillin in conjunction with an aminoglycoside in febrile neutropenic cancer patients [5]. Cefamandole has valuable activity against Klebsiella species; Staphylococcus aureus; and isolates of Enterobacter species, Serratia marcescens, and Escherischi coli resistant to earlier cephalosporins [ 141.…”
Section: Introductionmentioning
confidence: 99%